Análise da atuação das instituições financeiras no Instagram - Lorenzetti, Jaqueline (2022)
Internet and social networks have brought together the democratization of the media, making the sharing of information and knowledge accessible to everyone. Another important movement is social networking platforms foster business and entrepreneurship, through tools that assist companies to advertise their products and also sell. All this, many times through free tools and applications. Thesis’s “Analysis of the Performance of Financial Institutions on Instagram” aims to investigate among the actions practiced, the marketing efforts these institutions practice within the Instagram platform, either to communicate or sell their products and services to their customers and prospects. The reason why Instagram was chosen between other social network platforms is strictly related to a current growth rate that suggests higher preference among social network audiences, as presented later in the literature review and confirmed by the research survey of this thesis, where respondents report more enthusiasm and commitment onto their accounts. To carry out this study and develop a methodology for this thesis, the research was structured in five chapters properly organized, following the principles of the scientific method, in sequence: Literature review; Methodology; Empirical analysis through secondary data collected from the banks' public profiles on Instagram; Research by questionnaire and finally, a Case Study of Nubank. The profile analysis of the selected banks recorded the actions of Brazilian and Portuguese institutions, while the research inquiry aimed to test the conditional hypotheses and finally the case study of Nubank as a complementary investigation, since this bank stood out from the others for its massive performance on social networks, namely on Instagram.